2016
DOI: 10.1093/infdis/jiw569
|View full text |Cite
|
Sign up to set email alerts
|

The roles of unfolded protein response pathways in Chlamydia pathogenesis

Abstract: Chlamydia is an obligate intracellular bacterium that relies on host cells for essential nutrients and adenosine triphosphate (ATP) for a productive infection. Although the unfolded protein response (UPR) plays a major role in certain microbial infectivity, its role in chlamydial pathogenesis is unknown. We hypothesized that Chlamydia induces UPR and exploits it to upregulate host cell uptake and metabolism of glucose, production of ATP, phospholipids, and other molecules required for its replicative developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 47 publications
3
28
0
Order By: Relevance
“…The activation of the IRE1α arm of the UPR pathways by all chlamydial strains and serovars reflected the fact that it is the most conserved of all the three UPR arms in eukaryotes (36). We therefore confirmed and extended previous studies with primary mouse epithelial cells that all the three arms of UPR were activated by Chlamydia (19). Since UPR induction may involve cytoskeletal protein assembly and interaction with the master regulator (BiP) and transducers of UPR signaling especially IRE1α, and chlamydial T3SS effector proteins bind to cytoskeletal proteins (34), we tested the hypothesis that Tarp and CT228 are involved in UPR initiation.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…The activation of the IRE1α arm of the UPR pathways by all chlamydial strains and serovars reflected the fact that it is the most conserved of all the three UPR arms in eukaryotes (36). We therefore confirmed and extended previous studies with primary mouse epithelial cells that all the three arms of UPR were activated by Chlamydia (19). Since UPR induction may involve cytoskeletal protein assembly and interaction with the master regulator (BiP) and transducers of UPR signaling especially IRE1α, and chlamydial T3SS effector proteins bind to cytoskeletal proteins (34), we tested the hypothesis that Tarp and CT228 are involved in UPR initiation.…”
Section: Resultssupporting
confidence: 89%
“…We extended previous studies that the mouse agent of pneumonitis ( C. muridarum ) activated all the three arms of UPR (19), by establishing that different strains and serovars of Chlamydia induce UPR. Thus, the assessment of UPR induction in epithelial cells using the human C. trachomatis (Ct.) serovars D and L. or the murine strain C. muridarum , revealed that all the chlamydial strains activated the IRE1α arm of the UPR (Figure 1a).…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations